2019
DOI: 10.1038/s41586-019-1659-4
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of chromatin topology safeguards genome integrity

Abstract: To safeguard genome integrity in response to DNA double-strand breaks (DSB), mammalian cells mobilize the neighboring chromatin to shield DNA ends against excessive resection that could undermine repair fidelity and cause damage to healthy chromosomes 1. This form of genome surveillance is orchestrated by 53BP1, whose accumulation at DSBs triggers sequential recruitment of RIF1 and the shieldin-CST-Polα complex 2. How this pathway reflects and impacts on the three-dimensional (3D) nuclear architecture is not k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
127
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(143 citation statements)
references
References 34 publications
16
127
0
Order By: Relevance
“…Recently, Ochs et al has shown that genome topology plays important roles in safeguarding the genome integrity in response to the double strand breaks (33). In this report, we showed that the genome topology also influences the degree of spontaneous DNA damage.…”
supporting
confidence: 61%
“…Recently, Ochs et al has shown that genome topology plays important roles in safeguarding the genome integrity in response to the double strand breaks (33). In this report, we showed that the genome topology also influences the degree of spontaneous DNA damage.…”
supporting
confidence: 61%
“…Divergent one-sided loop extrusion hence takes place at the DSB, which in turn allows the locally-recruited ATM to phosphorylate H2AX containing nucleosomes as the chromatin fiber is pulled by the cohesin ring. Given that current estimates of cohesin-mediated loop extrusion suggest a rate of 0.5-2 kb per second in vitro 24,25 , such a mechanism would allow a rapid way to assemble DDR foci, with the entire megabase-sized chromatin domain being modified in about 10-30 min, which 9 fits with the observed rate of H2AX foci assembly 9 . This model would be in agreement with the recent finding that in yeast, the ATM ortholog Tel1 mediates H2A phosphorylation in a manner that agrees with a 1D sliding model rather than a 3D diffusion model 35 .…”
mentioning
confidence: 65%
“…As 53BP1 works together with the rest of its downstream cofactors to block over-resection of DNA DSBs, loss of any of these proteins partially restores RAD51 filament formation, functional HR and PARP-inhibitor resistance in BRCA1-deficient cells. Notably, whereas recruitment of RIF1, REV7 and SHLD1/2/3 depends on intact 53BP1, losing the downstream proteins does not prevent 53BP1 from forming IRIF [44][45][46][47] . Thus, in the absence of its co-factors, 53BP1 is still bound to DSB-proximal chromatin and therefore might interfere with efficient PALB2 recruitment, especially in BRCA1-deficient settings.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, in the absence of its co-factors, 53BP1 is still bound to DSB-proximal chromatin and therefore might interfere with efficient PALB2 recruitment, especially in BRCA1-deficient settings. Importantly, according to a recent study that employed super-resolution microscopy to characterise chromatin conformations orchestrated by 53BP1 and its co-factors, 53BP1 accumulates near DSB sites and, together with RIF1, forms topologically associating domains (TADs) of compacted chromatin 47 . Whereas the integrity of these TADs is fully dependent on 53BP1 and is partially compromised by RIF1 depletion, loss of Shieldin components does not affect 53BP1/ RIF1-mediated chromatin compaction 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation